Understanding Participation in Value Co-Creation and Acceptance of iPosyandu by Extending UTAUT among Community Health Workers - Azmii Lathifah; Utomo Sarjono Putro; Fedri Ruluwedrata Rinawan; Santi Novani; Valid Hasyimi; Adhya Rare Tiara (CommIT (Communication and Information Technology) Journal, 2023)
Digitalization is inevitable, including in the health sector. The iPosyandu, a mobile digital platform, is introduced to help the report of Community Health Workers (CHWs) and monitor the Pos Pelayanan Terpadu (Posyandu - Integrated Healthcare Center) data online. Unfortunately, CHWs still report data manually using paper, which takes a long time to store because some are still reluctant to change to digital services. Therefore, it is necessary to study CHWs’ intention to create new values and accept technology to sustain the application. The research aims to determine the factor influencing the intention to participate in value co-creation and use iPosyandu by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) among CHW. A Partial Least Square-Structural Equation Modelling (PLS-SEM) is conducted with a cross-sectional survey involving 222 CHWs in Purwakarta, Indonesia. The research finds that effort expectancy and perceived policy support significantly affect the intention to participate in value co-creation and usage of iPosyandu. The findings highlight that the critical role of intention to participate in value co-creation significantly affects the intention to use iPosyandu. The findings also suggest that policymakers and application developers should increase the use of iPosyandu by improving the effort systems, providing policy support, and facilitating CHWs to cocreate the value of the application to encourage them to use iPosyandu.